COMPETING MYCOFLORA WITH ASPERGILLUS FLA VUS IN KERNELS OF RABI AND KHARIF MAIZE CROPS OF BHAGALPUR - A K. CHOUDHARY, K. S. BILGRAMI AND (Indian Phytopathology, 2002)
In kernels of rabi and kharif maize crops, association patterns of various fungi along with Aspergillus flavus were determined (Chi square test in 2 x 2 table). 13 fungal species were identified which represented 78 possible pairings', among which 38 pairings were of significant negative associations, 3 pairings had significant positive associations and 37 pairings had non-significant associations. Fungal species identified in kernels of rabi crops had 36 pairings (out of 9 fungal species identified) in which 15 and 2 pairings had significant negative and significant positive associations respectively while 19 pairings had non- significant associations. Incidence of the toxigenic isolates of A. flavus were higher (42.95 per cent) in the kernels of kharif crops than the kernels of rabi crops (26.35 per cent).